Case Report: Pediatric respiratory viral infection failure: a case series of eight fatalities in children under 5 years old in Iran - Ramzali, Mahnaz; Samadizadeh, Saeed; Ebrahimi, Mohsen; Barati, Leila; Nakstad, Britt; Tahamtan, Alireza (Frontiers in Pediatrics, 2025)
Acute respiratory tract infection (ARTI) remains a major health threat to children under five, contributing to significant morbidity and mortality worldwide. According to the World Health Organization (WHO), ARTI leads to the hospitalization of over 12 million children annually, with approximately one million fatalities, one-third of which occur in low-income countries. The respiratory tract hosts diverse microorganisms, among which pathogenic viruses and bacteria are the leading causes of ARTI. Several risk factors—including age, gender, living conditions, seasonality, and underlying diseases—can influence disease severity. Documenting detailed case series that highlight the clinical characteristics and outcomes of pediatric ARTI, particularly in children with complex underlying conditions, is essential for understanding its impact and guiding clinical decision-making. This manuscript presents a case series of eight pediatric patients from Taleghani Children's Hospital in Gorgan, northern Iran, who tragically succumbed to respiratory viral infections, offering insights into the challenges of managing severe ARTI in children.